Identifying and quantifying initial post-discharge needs for clinical review of sick, newborns in Kenya based on a large multi-site, retrospective cohort study - Wainaina, John; Lee, Esther; Irimu, Grace; Aluvaala, Jalemba; English, Mike; , The Clinical Information Network Author Group; Mochache, Dolphine; Vitalis, Juma; Namayi, Arnest; Bonface, Nyumbile; Mochache, Dolphine; Soita, Samuel; et al. (Frontiers in Pediatrics, 2024)
Progress in neonatal care has resulted in a 51% decrease in global neonatal mortality rates from 1990 to 2017. Enhanced survival will put pressure on health care systems to provide appropriate post-discharge, follow-up care but the scale of need for such care is poorly defined.We conducted a retrospective cohort study of newborns discharged from 23 public hospital neonatal units (NBUs) in Kenya between January 2018 and June 2023 to identify initial follow-up needs. We first determined pragmatic follow-up categories based on survivors' clinical conditions and morbidities. We then used individual phenotypes of individual babies to assign them to needing one or more forms of specialized clinical follow-up. We use descriptive statistics to estimate proportions of those with specific needs and patterns of need.Among 136,249/159,792 (85.3%) neonates discharged, around one-third (33%) were low birth weight (<2500g), and a similar 33.4% were preterm (<37 weeks). We estimated 131,351 initial episodes of follow-up would be needed across nine distinct follow-up categories: general pediatrics, nutrition, growth & development (40.4%), auditory screening (38.8%), ophthalmology for retinopathy of prematurity (9.6%), neurology (8.0%), occupational therapy (1.3%), specialized nutrition (0.9%), surgery (0.8%), cardiology (0.2%), and pulmonary (<0.1%). Most neonates met the criteria for two (52.3%, 28,733), followed by three (39.6%, 21,738) and one follow-up episodes (5.6%, 3,098). In addition to prematurity and very low birth weight (≤1500g), severe infections with extended gentamicin treatment, severe jaundice managed with phototherapy, and hypoxic-ischemic encephalopathy (HIE) contributed substantially to the pattern of need for post-discharge follow-up.Almost half of surviving NBU infants have multiple specialty post-discharge follow-up needs. More urgent attention needs to be focused on healthcare planning now to guide strategies to address the varied medical and developmental needs that we outline in resource-constrained contexts like Kenya.